2013
DOI: 10.12659/ajcr.883793
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of acute type a aortic dissection in association with early open repair of acute limb ischemia may prevent aortic surgery

Abstract: SummaryBackground:Acute type A aortic dissection (AAAD) is a cardiovascular emergency with a high potential for death. Rapid surgical treatment is indicated to prevent fatal complications. Aggressive appropriate medical management starts at first suspicion and is essential to prevent exacerbation or rupture of the dissection. Despite improved surgical techniques, perioperative care and the development of specialized cardiovascular centers, mortality remains high. Organ ischemia is a catastrophic manifestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…When comparing pressure values, using the results shown in Fig. 5, the pressure gradient along the whole aorta is significantly decreased; this behaviour indicates the successful effect of antihypertensive drugs [12,16,30] The WSS is principally essential in the study of AD because of its direct effect on the vessel wall [4,5], which cannot be measured invasively or experimentally. However, CFD can provide a great insight into this parameter and its resultant indices [4,5,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing pressure values, using the results shown in Fig. 5, the pressure gradient along the whole aorta is significantly decreased; this behaviour indicates the successful effect of antihypertensive drugs [12,16,30] The WSS is principally essential in the study of AD because of its direct effect on the vessel wall [4,5], which cannot be measured invasively or experimentally. However, CFD can provide a great insight into this parameter and its resultant indices [4,5,29].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological therapy has been used prior to surgical treatment or endovascular treatment [12,16]. Historically, in the early 1960s, according to the results of Wheat and associates experiments, it was found that two principal goals of pharmacological therapy are diminution of left ventricular ejection force (dp/dt) and reduction in BP [12,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that ischemic events affecting other territories (such as lower limbs) may be the dominant clinical feature of AD [20]. Hence, the main symptom at presentation of AD may be not thoracic pain but ischemia of one or multiple organs, which may eventually lead to treatment directed to the affected territory.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate for untreated patients with AD after symptoms start is about 1% per hour. As a result, early diagnosis is required for proceeding with the most appropriate medical or surgical treatment options [1]. In one study, patients with AD had been misdiagnosed in 16% of cases presenting to the ER and AD was not even included in the initial differential diagnoses [2].…”
Section: Introductionmentioning
confidence: 99%